Genitourinary Anomalies in Patients with Anorectal Malformation - Abdullah, Farooq; Daraz, Muhammad; Saeed, Khawar; Ur Rahman, Fayaz; Uzair, Muhammad; Gulnaz, Nadia (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
objective To determine the frequency of genitourinary abnormalities in patients having anorectal malformations. Methodology This descriptive cross-sectional study was carried out in the Department of Pediatric Surgery, Khyber Teaching Hospital, Peshawar from August 2017 To February 2018. Any child (both genders) with a clinically apparent diagnosis of anorectal malformation having age 1 month or less (Neonate) was included in the study. Any patient who has undergone any surgical intervention elsewhere for anorectal malformation and cases of intersex or genital ambiguity were excluded. The level of the anorectal lesion was determined by radiographic evaluation. Renal ultrasound and intravenous-pyelography (IVP) and Voiding Cysto-uretherography (VCUG) were performed for urinary tract malformations in all cases with high-level anorectal lesions. In low-level anorectal lesions ultrasound was performed initially with IVP and VCUG performed later if needed to investigate any anomaly (dilated ureters, hydronephrosis) found on ultrasound. Results A total of 90 patients were included in this study. There were 68.89% males and females were 31.11%. The male to female ratio was 2.2:1. The average age of the patients was 5.03±6.11 days. The frequency of genitourinary abnormalities among children with anorectal malformations was found in 56(62.82%) patients with vesicoureteric reflux (VUR) being the most common anomaly (23.3%). Conclusion Anorectal Malformation patients should be screened for urogenital anomalies. Early detection of the associated anomalies will result in proper management and better outcome. Keywords: Anorectal malformations, Genitourinary anomalies, Vesicoureteric reflux